Scenario planning for an autonomous future: A comparative analysis of national preparedness of selected countries. (May 2021) - de Klerk, Yvette; Manuel, Michael Ekow; Kitada, Momoko
Abstract: This paper reports on the outcome of a comparative analysis of national preparedness relating to maritime policy, legislative frameworks, societal readiness and human resource development for autonomous vessel operations in selected countries. The study used a systematic literature review to generate four possible scenarios from which one was selected as the most plausible for interrogating the state of preparedness of the selected countries. A mixed methods approach was then used to gain in-depth insights into the legislative, human resource, and infrastructure aspects of national preparedness. The resulting analysis and findings, informed by a methodological consideration of various external factors, reveal the unique situation of each of the selected countries which either impedes or facilitates national preparedness. The existence (or non-existence) of a maritime transport policy together with its implementation (or non-implementation) of related actions regarding technological readiness reflect whether the conditions in the scenario will be a threat, challenge or opportunity for that particular country. Despite this, many countries appear not to have addressed the specific issue of readiness for an autonomous future in shipping, either because of a lack of awareness or because policy makers are pre-occupied with what is considered to be more pressing public policy matters. The paper concludes by noting that scenario planning, stakeholder identification and partnerships, as well as explicit policy development mechanisms geared towards close(r) collaboration between government, industry and academia as drawn from triple helix theory are required to successfully respond to the possible extreme disruption of autonomous systems in a maritime context. Highlights: Scenario planning as a mechanism in policy gap analysis. Scenario planning as an instrument to interrogate stakeholders' mindset. Triple helix collaboration to further public policy on autonomous shipping.